Effectiveness of Schema Therapy on Coping Styles and Quality of Life in Overweight Individuals with Binge Eating Disorder - Mardi , Turan; Zabihi , Rozita; Esmailzadeh, Zohreh (Health Nexus, 2025)
The aim of this study was to evaluate the effectiveness of schema therapy on coping styles and quality of life in overweight individuals with binge eating disorder. The research method was a semi-experimental design, with a pre-test-post-test structure and a control group. The statistical population consisted of all women with binge eating disorder who visited nutrition and weight control clinics in District 1 of Tehran. The sampling method was cluster sampling, where two clinics were selected from the nutrition and weight control clinics in District 1, and 50 individuals were chosen from each clinic. A binge eating questionnaire was distributed among 100 individuals. Based on the results of the test, 15 individuals with the highest binge eating scores were randomly assigned to the experimental group, and 15 individuals to the control group. The data collection tools in this study were the Binge Eating Questionnaire by Gormally, Black, Daston, and Rardin (1982), the Coping Styles Questionnaire by Endler and Parker (1990), and the Quality of Life Questionnaire by the World Health Organization (1993). Schema therapy was conducted in 20 sessions, each lasting 45 minutes. The data were analyzed using covariance analysis. The results showed that schema therapy had an impact on coping styles and quality of life in overweight individuals with binge eating disorder. These findings suggest that by changing and correcting maladaptive early schemas, individuals can adopt healthier and more effective coping styles instead of using ineffective ones, resulting in an improvement in their quality of life.